Rural infrastructure and the role of social capital in Serbia - Runia, Maaike; Bogdanov, Natalija; Heijman, Wim (Economics of Agriculture, 2010)
The starting point of this research is the assumption that infrastructural development in Serbia could be the key to economic growth. The aim of this research is to present an overview of the level of development in rural Serbia with a focus on infrastructure. The research compares twelve rural Serbian districts on the basis of data about the three categories economic performance, infrastructure development and social capital. Outcomes of the research are an analysis of the relations between the three categories and a comparison of the Serbian districts. The two main findings of this research are that the positive influence of infrastructure on economic development is not convincingly proven for Serbia and that the relation between economic development and social capital (measured by election data) turns out to be negative instead of positive.